1995
DOI: 10.1097/00003246-199502000-00015
|View full text |Cite
|
Sign up to set email alerts
|

A look into the nature and causes of human errors in the intensive care unit

Abstract: Objectives: The purpose of this study was to investigate the nature and causes of human errors in the intensive care unit (ICU), adopting approaches proposed by human factors engineering. The basic assumption was that errors occur and follow a pattern that can be uncovered. Design: Concurrent incident study. Setting: Medical-surgical ICU of a university hospital. Measurements and main results: Two types of data were collected: errors reported by physicians and nurses immediately after an error discovery; and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
1
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 704 publications
(109 citation statements)
references
References 8 publications
4
101
1
3
Order By: Relevance
“…The results of our study differ from the results of previous studies, supporting our hypothesis that anesthesia providers can highlight systems weaknesses and causal mechanisms in the ICU not identified by other personnel. As compared to previous work on critical incidents in the ICU by Donchin, et al , a larger proportion of near misses from our study occurred at night or on the weekend, [14] which could imply that decreased staffing in the ICU on off-hours impacts the ability of critical care providers to recognize, react to, and report near misses and adverse events. Additionally, the rate of technical errors in the ICU in our study was lower than previous estimates, [9] which was somewhat surprising given the technical role of the anesthesiologist in airway management and resuscitation.…”
Section: Discussioncontrasting
confidence: 62%
“…The results of our study differ from the results of previous studies, supporting our hypothesis that anesthesia providers can highlight systems weaknesses and causal mechanisms in the ICU not identified by other personnel. As compared to previous work on critical incidents in the ICU by Donchin, et al , a larger proportion of near misses from our study occurred at night or on the weekend, [14] which could imply that decreased staffing in the ICU on off-hours impacts the ability of critical care providers to recognize, react to, and report near misses and adverse events. Additionally, the rate of technical errors in the ICU in our study was lower than previous estimates, [9] which was somewhat surprising given the technical role of the anesthesiologist in airway management and resuscitation.…”
Section: Discussioncontrasting
confidence: 62%
“…Results in Table number (15) shows that all of the three Jordanian accredited private hospitals were consistent in ranking the five causes of incidents and to choose the Insufficient /Improper use of equipments as the most leading cause while Insufficient number of staffing as the least leading cause of incidents but with different percentages .…”
Section: Causes Of Incidentsmentioning
confidence: 93%
“…Referring a patient to a medical procedure without the information required reflects inadequate pattern communication that characterizes the complex health system. Previous studies [16,17] found that poor communication is a major cause of human errors in medical systems, and 50% of human errors reported by medical staff persons were caused by failures in transferring medical information [16]. These cause delays in providing medical treatment and may be the main obstacle to human errors prevention in medical care systems.…”
Section: Methodsmentioning
confidence: 99%
“…Standardization and homogeneous work procedures are essential because they structure the medical work environment, and enable the prediction of events during medical procedure performance [18]. In a study [17] that examined the nature of human errors in intensive care units, one of the major findings was lack of standardization - tubes, fluid bags, and drugs were insufficiently marked during performing the medical procedures. The researchers found that these problems caused staff members to improvise and develop their own style of working.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation